Possibilidades de educação em Astronomia para pessoas com deficiência visual - Correia, Cleison da Silva (IEAA - Instituto de Educação, Agricultura e Ambiente (Humaitá), 2022)
Academic astronomy and Cultural Astronomy are two areas with different perspectives of understanding skies. In Academic Astronomy, the study of celestial phenomena and bodies is culturally linked to vision, while in the cultural astronomy the Sky-Earth relationships are studied in a holistic, transdisciplinary way, without a single preferential sensory bias, which may bring an inclusive perspective about the knowledge of the skies. Thus, in the Inclusive Education context, from the bibliographic survey, this study, a qualitative approach, aimed to understand the State of Knowledge about Education in Astronomy, from the perspective of visually impaired people. For this survey, a time frame for the period of 2001 to 2021 was established in the following databases: National Symposium on Astronomy Education (SNEA, in Portuguese), Latin-American Magazine of Astronomy Education (RELEA, in Portuguese) and Bank of Theses and Dissertations on Education in Astronomy (BTDEA, in Portuguese). For the data codification and examination, the analysis of content technique is used. An increase of the number of works related to Astronomy Education for visually impaired people was observed in the last 10 years. Also, these works presented a practical-applicable and investigative-theoretical approach. It is believed that this research can contribute to the constitution of a survey that allows knowing more about this theme and its possible application and dissemination, contributing to motivating teachers in the initial and continuing education in Science Teaching, and to reflecting on the possibilities in an inclusive Astronomy Education from the Cultural Astronomy.